ARCTIC WINTER TESTS 1961, OF HATCH HOODS FOR COMBAT VEHICLES - BARNHART,ROGER D. (1961)
A universal hatch hood was installed on an M60 tank which was operated 1002 miles over various test courses in ambient temperatures ranging from +5 F to -31 F. Design, comfort, operation, durability and defrosting characteristics were observed. The hatch hoods tested are not suitable for use in the arctic without further improvements. It is recommended that the hood be redesigned to correct the deficiencies noted and retested under winter arctic conditions. (Author)